(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article presents a comparative analysis of the morphological systems of Classical Arabic and Modern Standard Arabic based on a dynamic-systemic approach. The study identifies the historical stability of the triliteral root model, pattern paradigms, verb forms, and noun derivation mechanisms. It also provides a scholarly explanation of the processes observed in the modern stage, including semantic expansion, changes in frequency of usage, and terminological renewal.